Korelasi Skor Gleason dengan Kadar Prostat Spesifik Antigen (PSA) Pada Pasien Karsinoma Prostat - Niniek Hardini (Faculty of Medicine, Universitas Andalas, 2021)
Prostatic carcinoma is malignancy of the prostate gland which is found in inferior portion of the bladder and anterior part of the rectum. To diagnose prostatic carcinoma, required Prostate Specific Antigen (PSA) levels and Gleason Score examination. PSA is an important marker serum for prostatic carcinoma. While the Gleason score is used to determine the differentiation degree and confirm the diagnosis of prostatic carcinoma. Objectives: This study was conducted to determine the correlation between PSA level with Gleason score in patients with prostatic carcinoma at Gatot Soebroto Army Hospital in period 2015-2016. Methods: The type of this study was analitic observational by cross sectional approach and consecutive sampling method with 60 subjects. The data was analyzed by using Spearman correlation test. Results: This study proved that there was a correlation between PSA level with Gleason score (p = 0,012; r = 0,321). Conclusions: PSA level had a relation to Gleason score.